2015
DOI: 10.1186/s13022-015-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous tranexamic acid as an adjunct haemostat to ornipressin during open myomectomy. A randomized double blind placebo controlled trial

Abstract: BackgroundMyomectomy is a surgical technique used for removal of uterine fibroids and historically hysterectomy has represented the mainstay of treatment. The options of conservative surgical approaches mainly aim at retention of fertility but have to be balanced against potential risks such as haemorrhage; blood loss at myomectomy still remains troublesome with use of various pharmacologic agents yielding inconclusive results. This trial aimed to explore the benefit of combining ornipressin and tranexamic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…TXA has been widely used in clinical treatment as a hemostatic agent, and it was included on the WHO list as an essential medicine in 2011 [29]. The safety of TXA has been confirmed in obstetric surgery, hip and knee joint replacement, coronary-artery and other surgeries [68]. The study of Benoni et al pointed out that TXA does not increase the risk of DVT, and it just inhibits fibrinolysis in the wound to play a hemostasis effect [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TXA has been widely used in clinical treatment as a hemostatic agent, and it was included on the WHO list as an essential medicine in 2011 [29]. The safety of TXA has been confirmed in obstetric surgery, hip and knee joint replacement, coronary-artery and other surgeries [68]. The study of Benoni et al pointed out that TXA does not increase the risk of DVT, and it just inhibits fibrinolysis in the wound to play a hemostasis effect [30].…”
Section: Discussionmentioning
confidence: 99%
“…TXA can block the lysine binding sites of plasminogen, plasmin, and tissue plasminogen activator to delay fibrinolysis and blood clot degradation [4, 5]. This drug has a significant hemostatic effect in obstetric surgery, hip or knee joint replacement, and coronary-artery surgery [68]. Previous meta-analyses have shown that TXA can significantly reduce blood loss in spinal surgery [912].…”
Section: Introductionmentioning
confidence: 99%
“…Tranexamic acid (TXA) is a synthetic amino acid analogue that acts as a competitive inhibitor of plasminogen and finally interferes with fibrinolysis [ 9 ]. TXA can decrease blood loss and reduce transfusion requirements, and has been successfully used in some surgical procedures including THA [ 8 , 10 12 ]. Intravenous or topical TXA administration for total hip arthroplasty has been demonstrated to be effective and safe in total hip arthroplasty [ 8 , 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ngichabe et al, in a randomised trial similarly reported on the correlation between myoma volume and blood loss at open myomectomy. 23 In our series, 74.8% of the patients had complications at myomectomy, based on Garry's criteria. 17 Primary intraoperative haemorrhage was the leading complication and 58.2% of the patients required blood transfusion.…”
Section: -22mentioning
confidence: 99%